PENERAPAN HUKUM DI TINGKAT PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA PENYELUNDUPAN MANUSIA (PEOPLE SMUGGLING) DI WILAYAH HUKUM KABUPATEN BENGKALIS - Ega Suzana; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The smuggling that occurs in Bengkalis District, Bengkalis Regency is due to the Bengkalis islands, so that there are many official and unofficial port lines directly bordering several neighboring countries such as Malaysia and Singapore.So it becomes a crossing in and out of people smuggling. Bengkalis District Police Department in 2019 succeeded in arresting 1 suspect and securing 8 (eight) people who came from Sumatra and Java. In 2018 the police also secured 4 suspects in human smuggling cases, all of whom were the majority of original Bengkalis residents.This type of research is classified as sociological research, because in this study the author directly conducts research at the location or place in order to provide a complete and clear picture of the problem under study. This research was conducted at Bengkalis Resort Police, while the population and sample are all parties related to the problem examined in this study, the source of the data used, primary data, and secondary data, and tertiary data, the data collection techniques in this study were carried out by interview, and literature study.The results of the study include: First, the investigation of human smuggling crimes in Bengkalis District handled by the Bengkalis District Police is not optimal. Second, the factors of this smuggling activity are organized, the mode of operation is interrupted, the budget, the lack of legal awareness in the community.Third, efforts to deal with human trafficking crimes that are effective and efficient in handling this case by conducting strict safeguards on official and unofficial channels, adding costs, completing facilities and infrastructure, providing protection to victims, and approaching the community regarding the dangers of smuggling crimes. human.Keywords: Invistigation-People Smuggling- suspect